Odpowiedzi

Najlepsza Odpowiedź!
2009-12-15T17:03:04+01:00
A.) 3m + n = 9
2m - 5n = -11

n=9-3m
2m-5n= -11

n=9-3m
2m-5(9-3m)=-11

n=9-3m
2m-45+15m=-11

n=9-3m
17m=-11+45

n=9-3m
17m=34/:17

n=9-3m
m=2

n=9-3*2
m=2

n=9-6
m=2

n=3
m=2

d.) 6x - 3y = 9
x + 5y = -9,5

6x - 3y = 9
x=-9,5-5y


6(-9,5-5y)=9
x=-9,5-5y

-57-30y=9
x=-9,5-5y

-30y=9+57
x=-9,5-5y

-30y=66 /:(-30)
x=-9,5-5y

y= -2,2
x=-9,5-5y

y= -2,2
x= -9,5-5*(-2,2)

y=-2,2
x=-9,5+11

y=-2,2
x=20,5







1 5 1
2009-12-15T17:06:47+01:00
A.)
3m + n = 9 / * -2
2m - 5n = -11 / * 3
-6m - 2n = -18
6m - 15n = - 33
+ -------------------
-17n=-51/ ÷ -17
n= 3
3m + 3 = 9
2m -5 *3 = -11
3m + 3 = 9
2m - 15 = -11
3m=9-3
2m-15= -11
3m=6 / ÷ 3
2m-15 = -11
m= 2
2*2 - 15 = -11
m=2
4-15 = -11
m=2
-11 = -11
m=2
n=3





1 5 1